Comparative evaluation of DNA synthesis for qPCR analysis from oral squamous cell carcinoma tissues - A rapid and robust isolation technique for gene expression studies - Ramya Mahalingam; Vivek Narayanan; Magesh Karuppur Thiagarajan; T. Jayaprakash; K.V. Leela (Oral Oncology Reports)
Background: DNA isolation from biological materials is the initial step in several bioanalytical processes, including the polymerase chain reaction (PCR). This procedure works best with pure DNA devoid of potential amplification reaction inhibitors. Since the quantity and quality of biological samples are limited, it is essential to extract as much DNA as possible from the original sample. The solid-phase extraction technique is frequently used to purify DNA. In this process, the DNA is adsorbed onto a solid support, any contaminants from the reaction are eliminated by washing, and the purified DNA is then eluted from the support. The quality and concentration of DNA have a direct effect on the gene analysis procedure. Therefore, before interpreting the results of PCR-based diagnostic assays, it is imperative to confirm the DNA preparation and integrity, particularly if no pathogenic DNA is identified. Methods: A comparative study was carried out using two standardized protocols for DNA synthesis in comparison with a test protocol incorporating carrier RNA and proteinase K from a viral detection kit. The quality and quantity of the synthesized DNA are assessed by qPCR analysis for gene amplification of metastasis suppressor genes NDRG1, RhoGDI, and KISS 1. Results and conclusion: The test protocol showed higher yields of DNA in comparison to the standard protocol. The concentration of DNA obtained was validated by the concentration of gene expressed from q PCR analysis. The gene expression was significantly higher when the test protocol method was followed for DNA synthesis. Thus the study validates the potential of nucleic acid carrier RNA molecules to improve DNA extraction processes used in tissue samples for gene analysis procedures.